(untitled) (Italian Journal of Public Health, 2007)
This article presents an overview of the conceptual development of school health promotion over the last twenty years. It also reflects on the changing inter-reaction between education and the health sector. It will show that the approach to school health promotion has become more setting-oriented, more complex in its intervention, more salutogenetic in its direction and more evidence based. The Health Promoting School as a setting approach has emerged and been recognised by several reviews as the most successful and therefore most recommended. In reality however, everyday school-life health-intervention of this type occurs rarely. It will be shown that after more than 10 years of piloting school health promotion, a paradigm shift has evolved in reaction to such disappointing developments. School health promotion today is linked directly to school educational development and school´s educational goals, at least in some European countries. Health intervention is conceptualized as a promoter of education in schools. The good and healthy school is the new core concept.